N‐substituted Piperazinopyridylsteroid Derivatives as Abiraterone Analogues Inhibit Growth and Induce Pro‐apoptosis in Human Hormone‐independent Prostate Cancer Cell Lines. (16th October 2013) - Brossard, Dominique; Zhang, Ying; Haider, Shozeb M.; Sgobba, Miriam; Khalid, Mohamed; Legay, Rémi; Duterque‐Coquillaud, Martine; Galera, Philippe; Rault, Sylvain; Dallemagne, Patrick; Moslemi, Safa; El, Laïla
<x xml:space="preserve">Abstract</x> Nine new 17‐(piperazin‐1‐yl)pyridin‐5‐yl)steroids as abiraterone analogues were synthesized. Compounds 5d and 5g showed selective activities against 17α‐hydroxylase/C17, 20‐lyase (CYP17A1) and aromatase (CYP19), respectively. IC50 values of 5d were 5.09 and >50 μm, whereas these values for 5g were >50 μm and 7.40 μm, respectively, for CYP17A1 and CYP19. Molecular modelling highlighted that the inhibitor designed to bind cytochrome P450 haem iron is a necessary condition but not the only rationale to explain inhibitory activity. These abiraterone analogues were then evaluated on hormone‐independent prostate cancer cell lines DU‐145 and PC‐3 and on hormone‐dependent breast and prostate cancer cell lines MCF‐7 and LNCaP, respectively. Compounds 5e, 5g and 5i have showed potent activities only on hormone‐independent prostate cancer cell lines DU‐145 and PC‐3 with 60–85% inhibition of both cell viability and growth at 10 nm with pro‐apoptotic mechanism as illustrated in PC‐3 cells by DNA ladder assay and Western blotting of Bax, Casp‐3 and its substrate, the poly (ADP–ribose) polymerase. We conclude that hybrid heterocycle steroids could be good lead compounds in the drug design especially against hormone‐independent prostate cancer.